2016
DOI: 10.1016/j.cviu.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Interactive multiple object learning with scanty human supervision

Abstract: We present a fast and online human-robot interaction approach that progressively learns multiple object classifiers using scanty human supervision. Given an input video stream recorded during the human-robot interaction, the user just needs to annotate a small fraction of frames to compute object specific classifiers based on random ferns which share the same features. The resulting methodology is fast (in a few seconds, complex object appearances can be learned), versatile (it can be applied to unconstrained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…2-d). This contrasts with other works based on ferns where they remain fixed throughout the training [39,52,54]. As a result, WiLFs are improved progressively with new available data given that the classifier is adapted at each time instance to new and unknown faces images and imaging conditions.…”
Section: Related Work and Contributionsmentioning
confidence: 96%
See 2 more Smart Citations
“…2-d). This contrasts with other works based on ferns where they remain fixed throughout the training [39,52,54]. As a result, WiLFs are improved progressively with new available data given that the classifier is adapted at each time instance to new and unknown faces images and imaging conditions.…”
Section: Related Work and Contributionsmentioning
confidence: 96%
“…Although this sort of learning allows to compute object models incrementally without using human annotations about the object location, self-learning is prone to drifting 3 and thus it deteriorates the performance of the classifier. To cope with this problem, methods commonly use object model priors [17], temporal consistency [15,23], and human assistance to disambiguate those difficult cases where the classifier is uncertain [54,57].…”
Section: Related Work and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, simple binary features computed on the intensity domain have been shown to accurately capture the varying appearance of a target object. Classifiers like Random Trees, Forests or Ferns [21], [23], [29], [38], [45], [56], [57] have then been proposed for matching these features very quickly, yielding similar results as those obtained with SIFT [32]. However, most of these methods only tackle problems with single object instances, and do not generalize to complete categories.…”
Section: Related Workmentioning
confidence: 99%
“…Yet, it has been shown that if several training images of the object are available, its appearance can be accurately modeled using simple classifiers built from hundreds of binary features. Decision Trees or Random Ferns are used for this purpose, and allow for real time object detection [23], [29], [38], [57].…”
Section: Introductionmentioning
confidence: 99%